Marine fungi from mangroves of Malaysia - Siti Aisyah Alias; Jones, E. B. Gareth (Evan Benjamin Gareth) 1937- (Monograph series (Universiti Malaya. Institute of Ocean and Earth Sciences), 2009)
This monograph is the result of 25 years of studying the marine mangrove fungi of Malaysia, during which circa 300 species have been documented. These studies have included the taxonomy of marine fungi and the description of new taxa, their ultrastructure, ecology, and the production of new bioactive compunds.